Relationship between Project Managers Personality and Small Public Construction Project Success in Malaysia - Mohd Noor, Syaharudin Shah; Esa, Muneera (International Journal of Sustainable Construction Engineering and Technology, 2021)
In the field of project management, particularly the construction industry in Malaysia, there are two key factors in determining the progress of a project, namely technical and non-technical skills. Accordingly, this study aims to explore the personality (non-technical skills) among Malaysian project managers on the success of small public construction projects. Using the Five Factor Theory (FFT) as a basis, this study uses two sets of measuring instruments for examining project manager’s personality and project success, the Big Five Inventory (BFI) and the Project Success Achieved (PSA). The questionnaire was distributed to two major organizations in Malaysia, the Implementation Coordination Unit, Prime Minister’s Department (ICU JPM) and Ministry of Rural Development (KPLB), which involved 137 project managers. The obtained data were analyzed using PLS-SEM and results indicate that the project manager’s personality has a significant impact on the success of SPCP where Conscientiousness (CT) and Agreeableness (AG) had a more prominent influence compared to other traits. This study provides theoretically meaningful relationships and valuable insights into construction management via personality element to ensure that national development objectives are achieved.